2017
DOI: 10.1002/zoo.21370
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental and visitor variables on the behavior of free‐ranging ring‐tailed lemurs (Lemur catta) in captivity

Abstract: The effect of the zoo environment on captive animals is an increasingly studied area of zoo research, with visitor effects and exhibit design recognized as two of the factors that can contribute to animal welfare in captivity. It is known that in some situations, visitors may be stressful to zoo-housed primates, and this may be compounded by environmental factors such as the weather, the time of day, and zoo husbandry routines. Exhibit design and proximity of the public are also known to influence behavioral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Similar to season, these findings highlight the importance of accounting for environment in the study of reptile behavior. Recently, both Collins et al (2017) and Goodenough et al (2019) reported that the behavior of ring tailed lemurs was better predicted by weather and time of day than visitor presence alone [19,20]. Furthermore, as many studies of visitor effect are correlational, it is also important to consider that visitor presence itself may be predicted by environmental variables such as temperature and time of day, thus evaluating environmental variables may provide additional context for understanding the nuances associated with visitor presence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to season, these findings highlight the importance of accounting for environment in the study of reptile behavior. Recently, both Collins et al (2017) and Goodenough et al (2019) reported that the behavior of ring tailed lemurs was better predicted by weather and time of day than visitor presence alone [19,20]. Furthermore, as many studies of visitor effect are correlational, it is also important to consider that visitor presence itself may be predicted by environmental variables such as temperature and time of day, thus evaluating environmental variables may provide additional context for understanding the nuances associated with visitor presence.…”
Section: Discussionmentioning
confidence: 99%
“…Goodenough et al (2019) recently reported that for ring-tailed lemurs (Lemur catta) in a walk-through exhibit, a situation where a visitor effect may be greater compared to traditional stand-and-view exhibits, time and weather were significant predictors of behavior, and the presence of both reduced the overall statistical effect of visitor presence [19]. Similarly, Collins et al (2017) found that visitors had limited effects on ring-tailed lemur behavior, while season, weather and time of day had strong effects on behavior [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This further supports our interpretation that visitors may be fear-provoking for little penguins in this exhibit. Research has shown that an area in which to retreat may minimise visitor-induced stress on zoo animals by providing a level of choice and control over their interactions with visitors [61][62][63][64]. Similarly, increased separation between visitors and penguins has shown to minimise the effects of visitors on little penguin fear responses [3].…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al [28] and Collins et al [29] found that crown lemurs ( Eulemur coronatus ) and ring-tailed lemurs ( Lemur catta ) adapted well and became habituated to visitor presence in their free ranging exhibits. Similarly, Martin and Melfi [30] reported that unfamiliar keeper presence did not appear to have detrimental effect on captive wild animal welfare for a number of species including slender tailed meerkat ( Suricata suricatta ).…”
Section: The Potential Impacts Of Avis On Wild Animal Welfarementioning
confidence: 99%